2018
DOI: 10.1152/jn.00638.2018
|View full text |Cite
|
Sign up to set email alerts
|

Direct assessment of presynaptic modulation of cortico-striatal glutamate release in a Huntington’s disease mouse model

Abstract: Glutamate is the main excitatory neurotransmitter in the brain, and impairments in its signaling are associated with many neurological disorders, including Huntington’s disease (HD). Previous studies in HD mouse models demonstrate altered glutamate receptor distribution and signaling at cortico-striatal synapses, and some studies suggest that glutamate release is altered; however, traditional methods to study synaptic glutamate release are indirect or have poor temporal resolution. Here we utilize iGluSnFR, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…A heatmap depicting representative iGluSnFR responses to 2, 20, and 50 pulses is shown in Figure 1B, and average iGluSnFR responses to 2, 20, and 50 pulses are shown in Figures 1C-E, respectively. Response peaks, indicative of the relative amount of glutamate released (Koch et al, 2018), were not significantly different in saline compared to ceftriaxone-treated mice, although a strong non-significant trend toward a reduction in iGluSnFR peaks was observed in the ceftriaxone group. As expected, there was a significant effect of the number of pulses, with longer 100 Hz stimulations generating larger iGluSnFR peaks (Figure 1F, saline n = 14, ceftriaxone n = 16, two-way RM ANOVA, treatment p = 0.084, # of pulses p < 0.001, interaction p = 0.330).…”
Section: Ceftriaxone Effects On Glt-1 Expression and Glutamate Dynamimentioning
confidence: 69%
“…A heatmap depicting representative iGluSnFR responses to 2, 20, and 50 pulses is shown in Figure 1B, and average iGluSnFR responses to 2, 20, and 50 pulses are shown in Figures 1C-E, respectively. Response peaks, indicative of the relative amount of glutamate released (Koch et al, 2018), were not significantly different in saline compared to ceftriaxone-treated mice, although a strong non-significant trend toward a reduction in iGluSnFR peaks was observed in the ceftriaxone group. As expected, there was a significant effect of the number of pulses, with longer 100 Hz stimulations generating larger iGluSnFR peaks (Figure 1F, saline n = 14, ceftriaxone n = 16, two-way RM ANOVA, treatment p = 0.084, # of pulses p < 0.001, interaction p = 0.330).…”
Section: Ceftriaxone Effects On Glt-1 Expression and Glutamate Dynamimentioning
confidence: 69%
“…Further studies are needed to clarify the extent of changes in dopamine levels over disease progression, particularly at early stages. In studies of glutamate dynamics in HD, the creation of glutamate sensing fluorescent reporters has allowed researchers to directly compare glutamate transmission between WT and HD mice (Koch, Woodard, & Raymond, ; Parsons et al, ). Similarly, new optogenetic sensors for real‐time imaging of dopamine dynamics (Patriarchi et al, ; Sun et al, ) could be used to directly assess dopamine dynamics in HD striatum.…”
Section: Altered Dopamine Signaling In Hd Mouse Modelsmentioning
confidence: 99%
“…Compelling animal data have demonstrated that striatal degeneration in HD may be secondary to excessive activation of glutamate-gated ion channels. 38 In studies of a neuron-like cell line, antioxidants were found to be able to protect against glutamate-induced cytolysis. 39 Two lipophilic, centrally active antioxidants were studied in HD: d-alpha-tocopheral (vitamin E) and idebenone.…”
Section: Resultsmentioning
confidence: 99%